Fortalecimiento lingüístico para el turismo rural en San Ramón de La Virgen de Sarapiquí - Hernández-Salazar, Ana Gabriela (2026)
The Agrotourism and Multiple Services Cooperative of San Ramón de La Virgen de Sarapiquí R.L. (COOPROTURS R. L.) brings together 33 entrepreneurs who have developed rural tourism projects in their communities. Following the completion of an English training program in 2024—born from an extension project titled “Strengthening English Language Competencies of the members of COOPROTURS R. L. for the development of rural tourism”—a need was identified for written materials translated into English to attract international visitors. In response, an extension strengthening activity was launched to support members in the professional translation of booklets, menus, signs, and other materials through a community diagnosis of translation needs, participatory processes, and a training process. Additionally, entrepreneurs were assisted through the creation of physical and digital promotional graphic materials for their businesses, both in English and Spanish. This initiative aims to contribute to the economic and cultural development of the community. This article intends to showcase the systematized process of collaboration between extensionists and entrepreneurs, while reflecting on the importance of follow-up processes with communities that have benefited from university extension projects.